Quality evaluation of metabolic and bariatric surgical guidelines - Qin, Zi-Han; Yang, Xin; Zheng, Ya-Qi; An, Li-Ya; Yang, Ting; Du, Yu-Lu; Wang, Xiao; Zhao, Shu-Han; Li, Hao-Han; Sun, Cheng-Kai; Sun, Da-Li; Lin, Yue-Ying (Frontiers in Endocrinology, 2023)
Objective To evaluate the quality of surgical guidelines on bariatric/metabolic surgery. Methods Four independent reviewers used the AGREE II (The Appraisal of Guidelines for Research and Evaluation II) tool to assess the methodological quality of the included guidelines and conducted a comparative analysis of the main recommendations for surgical methods of these guidelines. Results Nine surgical guidelines were included in this study. Five articles with AGREE II scores over 60% are worthy of clinical recommendation. The field of rigor of development was relatively low, with an average score of 50.82%. Among 15 key recommendations and the corresponding best evidence in the guidelines, only 4 key recommendations were grade A recommendations. Conclusions The quality of metabolic and bariatric guidelines is uneven, and there is much room for improvement.